Design, synthesis and biological characterization of selective LIMK inhibitors. Issue 18 (15th September 2015) - Boland, Sandro; Bourin, Arnaud; Alen, Jo; Geraets, Jacques; Schroeders, Pieter; Castermans, Karolien; Kindt, Nele; Boumans, Nicki; Panitti, Laura; Vanormelingen, Jessica; Fransen, Silke; Van de Velde, Sarah; et al.
Graphical abstract